O6D.3 Evaluation of polycyclic aromatic hydrocarbons exposure across occupations in korea using urinary metabolite 1-hydroxypyrene. (April 2019) - Koh, Dong-Hee; Park, Ju-Hyun; Lee, Sang-Gil; Kim, Hwan-Cheol; Choi, Sang-Jun; Jung, Hyejung; Park, Dong-Uk
Abstract : Objectives: Polycyclic aromatic hydrocarbons are a well-known carcinogen causing lung and skin cancers in exposed workers. Several occupations such as coke production have been reported to be associated with high PAHs exposure. However, previous reports have been confined in several occupations. Thus, we aimed to evaluate PAHs exposure across a wide range of occupations using its urinary metabolite 1-hydroxypyrene (1-OHP). Methods: To evaluate PAHs exposure across occupations, we collected the urine 1-OHP data from the Korean National Environmental Health Survey which is a nationwide bio-monitoring survey. The data contained information about urine 1-OHP levels, cigarette smoking status, and standard occupational codes. We calculated summary statistics of urine 1-OHP levels for each occupation. In addition, we calculated the relative exposure indicators which are the proportions of exceeding the quartile levels. Since cigarette smoking is a single most influential factor of PAHs exposure, we repeated the analyses by excluding current smokers. Results: Overall geometric means (GM) of all populations and non-smoker populations were 0.13µg/L and 0.10µg/L, respectively. For the major group of occupation, 'Craft and Related Trades Workers' and 'Equipment, Machine Operating and Assembling Workers' showed the highest urine 1-OHP levels, while 'Homemaker' showed the lowest level. For the sub-major group of occupation, 'Video and Telecommunications Equipment Related Occupations' showed the highest percentage (61%) of exceeding the third quartile (Q3) level of all populations. While 'Legal and Administration Professional Occupations' showed the lowest percentage of exceeding the Q3 level of all populations. For the minor group of occupation, 'Horticultural and Landscape Workers' showed the highest percentage (64%) of exceeding the Q3 level of all populations. While 'Kindergarten teachers' showed the lowest percentage of exceeding the Q3 level of all populations. Conclusions: Our results will provide ancillary information about PAHs exposure across occupations, especially in occupations where PAHs exposure has not well known.